(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Despite recent advances in the care of patients with acute coronary disease and the benefits associated with the early use of reperfusion strategies, cardiogenic shock as a complication of acute myocardial infarction continues to be associated with a dismal prognosis. There is a strong relationship between serum cardiac troponin I with cardiogenic shock as a complication of acute myocardial infarction. A case control study was designed to see the association of serum cardiac troponin I with cardiogenic shock. The study was done from July 2008 to June 2009. Sixty subjects were selected as study population which were taken from department of Cardiology, Mymensingh Medical College hospital, Mymensingh. Among them 30 were diagnosed case of cardiogenic shock and 30 were age and sex matched control. It revealed that the mean cardiac troponin- I levels in case group were 15.998±28.31 ng/ml and control group were 0.065 ± 0.08 ng/ml respectively. The study suggest that serum cardiac troponin- I level is significantly associated with cardiogenic shock. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16017 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 21-23